Investigation of alcohol-related social norms among youth aged 14–17 years in Perth, Western Australia: protocol for a respondent-driven sampling study. Issue 10 (22nd October 2013) - Hildebrand, Janina; Maycock, Bruce; Howat, Peter; Burns, Sharyn; Allsop, Steve; Dhaliwal, Satvinder; Lobo, Roanna
Abstract : Introduction: Alcohol use among young people is a major public health concern in Australia and internationally. Research elucidating social norms influencing alcohol use supports the desire to conform to peers. However, there is a lack of evidence on how social norms are transmitted from the community to young people and between family members and peers, as previous studies are limited to mainly school and university environments. This article describes the proposed process to investigate common alcohol-related norms held by 14-year-olds to 17-year-olds in Perth, Western Australia, and to clarify the process and pathways through which proalcohol norms are transmitted to adolescents. Methods and analysis: This cross-sectional quantitative study will use respondent-driven sampling (RDS) to recruit a sample of 672 adolescents from sporting groups, youth programmes and the community in Perth. Data will be collected with a previously developed and validated multidimensional online survey instrument. A variety of strategies will be explored to aid participation including face-to-face recruitment and survey administration, web-based RDS and a 'mature minor' consent assessment protocol. Data analysis will include descriptive statistics of demographic characteristics, as well as social network and dyadic analyses, to explore the connections between shared understanding of norms and behaviours among individuals and how these translate into reported practices. Ethics and dissemination: This research is expected to extend our understanding of normative development pathways to inform future interventions, and will be widely disseminated through conference presentations, peer-reviewed papers, media channels and community seminars. A study reference group of key health industry stakeholders will be established to encourage integration of study findings into policy and practice, and results will guide the development of community interventions. The Curtin University Human Research Ethics Committee has granted approval for this research.